2020
DOI: 10.1021/acs.jafc.0c03257
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Peroxidase from Foxtail Millet Bran on Colitis-Associated Colorectal Carcinogenesis by the Blockage of Glycerophospholipid Metabolism

Abstract: Abnormal glycerophospholipid (GPL) metabolism represented by phosphatidylcholine (PC) and phosphatidylethanolamine (PE) has been as a universal metabolic hallmark of cancer, which is involved in tumor progression. Our previous finding showed that peroxidase from foxtail millet bran (FMBP) exhibited significant anticolorectal cancer (CRC) activity in vitro and in nude mice. Presently, the potential of FMBP in clinical application was further evaluated by an azoxymethane (AOM)/dextran sodium sulfate (DSS)-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Since homologous recombination-de cient cells are sensitive to poly(ADP-ribose) polymerase (PARP) inhibitors, they have attracted clinical interest (31). Abnormal glycerophospholipid (GPL) metabolism is a common metabolic hallmark of cancer and is associated with tumor progression, which is represented by phosphatidylethanolamine (PE) and phosphatidylcholine (PC) (32). Some studies have shown elevated PC levels in most cancers, including brain(33, 34), breast (35, 36), ovarian (37), cervical(38), endometrial (39) and prostate(40) cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Since homologous recombination-de cient cells are sensitive to poly(ADP-ribose) polymerase (PARP) inhibitors, they have attracted clinical interest (31). Abnormal glycerophospholipid (GPL) metabolism is a common metabolic hallmark of cancer and is associated with tumor progression, which is represented by phosphatidylethanolamine (PE) and phosphatidylcholine (PC) (32). Some studies have shown elevated PC levels in most cancers, including brain(33, 34), breast (35, 36), ovarian (37), cervical(38), endometrial (39) and prostate(40) cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation caused by inflammatory bowel disease (IBD), including ulcerative colitis and Crohn's disease, plays a critical role in tumorigenesis of the gastrointestinal tract (Lichtenstern et al, 2020). Mechanistically, DNA hypermethylation, reactive oxygen species (ROS) production and gut microbiota imbalance facilitate IBD, subsequently leading to the initiation and progression of colitisassociated carcinogenesis (CAC) (Rogler, 2014;Gagnière et al, 2016) The results speculated that FMBP blocked GPL metabolism by reducing the expression levels of key metabolic enzymes involved in phosphatidylcholine and phosphatidylethanolamine (such as PCYT1α and PCYT2), resulting in insufficient adenosine triphosphate to maintain CRC growth (Shan et al, 2020).…”
Section: Metabolomicsmentioning
confidence: 99%
“…Along with its superior nutritional properties and documented anti-inflammatory function, foxtail millet is also rich in non-nutrient prebiotics, such as polyphenols and dietary fibers ( 22 ), suggesting its possible positive effects on the gut microbiota and IBD. Bond polyphenols and peroxidase of foxtail millet bran have also been reported to inhibit colitis-induced carcinogenesis in a mouse model ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%